Correlated states in β-Li2IrO3 driven by applied magnetic fields. Issue 1 (December 2017) - Ruiz, Alejandro; Frano, Alex; Breznay, Nicholas; Kimchi, Itamar; Helm, Toni; Oswald, Iain; Chan, Julia; Birgeneau, R.; Islam, Zahirul; Analytis, James
Abstract Magnetic honeycomb iridates are thought to show strongly spin-anisotropic exchange interactions which, when highly frustrated, lead to an exotic state of matter known as the Kitaev quantum spin liquid. However, in all known examples these materials magnetically order at finite temperatures, the scale of which may imply weak frustration. Here we show that the application of a relatively small magnetic field drives the three-dimensional magnet β-Li2 IrO3 from its incommensurate ground state into a quantum correlated paramagnet. Interestingly, this paramagnetic state admixes a zig-zag spin mode analogous to the zig-zag order seen in other Mott-Kitaev compounds. The rapid onset of the field-induced correlated state implies the exchange interactions are delicately balanced, leading to strong frustration and a near degeneracy of different ground states. Materials with a Kitaev spin liquid ground state are sought after as models of quantum phases but candidates so far form either zig-zag or incommensurate magnetic order. Ruiz et al. find a crossover between these states in β-Li2 IrO3 under weak magnetic fields, indicating strongly frustrated spin interactions.